Perovskite battery component and method of preparation

By employing low-temperature pre-crystallization and high-temperature annealing, the damage to perovskite solar cell modules during laser etching was reduced, device efficiency and stability were improved, and the problem of thin film damage caused by laser etching was solved.

CN116669506BActive Publication Date: 2026-11-06TRINA SOLAR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310436470.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-21
Publication Date
2026-11-06
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

In the fabrication process of perovskite solar cell modules, laser etching can easily damage the perovskite film, producing edge burrs and craters, which affect device efficiency and long-term stability. Furthermore, lead dust poses a significant health hazard.

Method used

A perovskite semi-dry film is formed by low-temperature pre-crystallization, and then laser scribing is performed on the semi-dry film. This is followed by high-temperature annealing to reduce laser etching damage and repair some of the damage.

Benefits of technology

It effectively reduces damage during the laser etching process, improves the efficiency and long-term stability of the battery module, avoids dust formation, and promotes uniform coverage of the charge extraction layer and buffer layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116669506B_ABST
    Figure CN116669506B_ABST
Patent Text Reader

Abstract

This invention relates to a perovskite solar cell module and its fabrication method. The fabrication method includes the following steps: a perovskite semi-dry film preparation step: forming a perovskite wet film on a first charge transport layer using perovskite ink, and then subjecting the perovskite wet film to low-temperature pre-crystallization to obtain a perovskite semi-dry film; wherein the low-temperature pre-crystallization temperature is 30–55°C and the time is 1–10 min; a laser scribing step: performing laser scribing on the perovskite semi-dry film to obtain a perovskite film with laser-scribed grooves. In the fabrication of the perovskite solar cell module, this invention first obtains a perovskite semi-dry film through low-temperature pre-crystallization, and then performs laser scribing on the perovskite semi-dry film, which effectively reduces the damage to the perovskite film caused by the laser etching process, thereby effectively improving the device's efficiency and long-term stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to perovskite solar cells, and more specifically to a perovskite solar cell module and its preparation method. Background Technology

[0002] With the increasing depletion of traditional fossil fuels, the global energy demand for rapid growth can no longer be met, making the search for new, clean, and alternative energy sources both necessary and urgent. Against this backdrop, third-generation solar cells, using perovskite-type organic-inorganic hybrid halide semiconductor materials as the light-absorbing layer, have seen rapid development. These cells have attracted significant attention from academic and industrial circles both domestically and internationally due to their advantages such as high absorption coefficient, long carrier diffusion length, solution-processability, and low cost. In just a few years, the certified efficiency of perovskite solar cells has exceeded 25.7%.

[0003] Perovskite solar cells, as a type of thin-film battery, are manufactured using a process similar to traditional copper indium gallium selenide (CIGS) and cadmium telluride (CdTe) solar modules. The series and parallel connection of sub-cells requires multiple laser scribing processes. Due to the inherent susceptibility of the perovskite light-absorbing layer material, conventional P2 laser etching processes easily generate dust, which can contaminate the laser lens and reduce focusing accuracy. More importantly, the laser etching scribing process can lead to edge burrs and crater formation in the perovskite layer, resulting in low device efficiency and poor long-term stability.

[0004] Currently, the large-area fabrication of perovskite modules for industrial applications typically involves high-temperature annealing and crystallization to obtain a dry thin film, followed by P2 laser etching. However, conventional P2 laser etching generates significant amounts of dust, contaminating the laser lens. Furthermore, perovskite materials contain lead, and this lead-containing dust poses a significant health hazard. Perovskite thin films are also susceptible to damage from high-energy lasers, and P2 laser etching easily leads to edge curling, burrs, and burn marks, affecting device efficiency and long-term stability. Edge curling and burrs can also hinder the uniform adhesion of the passivation and compact layers to the laser-cut surface. Damage caused by conventional thin films after P2 laser etching cannot be repaired by high-temperature annealing and crystallization. Therefore, minimizing the damage and other adverse consequences of laser etching during the fabrication of perovskite solar cell modules is a pressing technical challenge. Summary of the Invention

[0005] This invention provides a perovskite solar cell module and its preparation method. The purpose of the invention is to reduce laser scribing damage in large-area perovskite solar cell modules and improve the performance of the solar cell modules.

[0006] In a first aspect, the present invention relates to a method for preparing a perovskite solar cell module, the method comprising the following steps: a perovskite semi-dry film preparation step: forming a perovskite wet film on a first charge transport layer by perovskite ink, and then subjecting the perovskite wet film to low-temperature pre-crystallization to obtain a perovskite semi-dry film; wherein the low-temperature pre-crystallization temperature is 30-55°C and the time is 1-10 min; a laser scribing step: performing laser scribing on the perovskite semi-dry film to obtain a perovskite film with laser scribing grooves.

[0007] Optionally, the preparation method further includes a high-temperature annealing step after the laser scribing step: subjecting the perovskite film with laser scribing grooves to high-temperature annealing to obtain a high-temperature annealed perovskite film.

[0008] Optionally, the high-temperature annealing temperature is 100-150℃ and the time is 1-30 min.

[0009] Optionally, the chemical formula of the perovskite material in the perovskite film after high-temperature annealing is ABX3, where A is selected from FA. + MA + and Cs + One or more combinations of B, where B is Pb 2+ and / or Sn 2+ X is selected from CI - ,Br - and I - One or more combinations thereof.

[0010] Optionally, the perovskite ink is prepared by mixing raw materials containing AX, BX2 and a solvent, wherein the minimum concentration of A, B and 1 / 3 of X in the perovskite ink is 0.7-2 mol / L.

[0011] Optionally, the thickness of the perovskite film after high-temperature annealing is 1–5000 nm and the band gap is 1.2–2.3 eV.

[0012] Optionally, the preparation method further includes the following steps after the high-temperature annealing step: sequentially preparing a second charge transport layer, a buffer layer, and a second electrode on the perovskite film after high-temperature annealing; and / or, the preparation method further includes the following steps before the perovskite semi-dry film preparation step: preparing the first charge transport layer on the first electrode, and then performing laser scribing on the first charge transport layer; or, performing laser scribing on the first electrode, and then depositing the first charge transport layer.

[0013] Optionally, the first charge transport layer and the second charge transport layer are selected from different types of electron transport layers and hole transport layers, respectively; the first charge transport layer and the second charge transport layer are each independently prepared by solution method, thermal evaporation method, sputtering method or atomic layer deposition method; and / or, the hole transport layer comprises NiO. x The electron transport layer is selected from one or more combinations of CuFeO2, CuAlO2, CuSCN, Cu2O, WO3, CuI2, MoS2, FeS2, P3HT, Spiro-meoTAD, Spiro-TTB, Poly-TPD, PFN, PEDOT, PSS, and PTAA, wherein 0.1 ≤ x ≤ 10; and / or, the electron transport layer is selected from TiO2, SnO2, ZnO, ZrO2, In2O3, CdS, CdSe, BaSnO3, Nb2O5, C 60 A combination of one or more of PCBMs.

[0014] Optionally, the first electrode and the second electrode are each independently selected from one or more combinations of Cu, Al, Ag, Au, ITO, IZO, FTO and IWO.

[0015] In a second aspect, the present invention relates to a perovskite solar cell module, which is obtained by the preparation method described in the first aspect.

[0016] Beneficial effects:

[0017] In the process of preparing perovskite solar cell modules, this invention first obtains a perovskite semi-dry film through low-temperature pre-crystallization, and then performs laser etching on the perovskite semi-dry film. This can effectively reduce the damage to the perovskite film caused by the laser etching process, thereby effectively improving the efficiency and long-term stability of the device. Attached Figure Description

[0018] Figure 1 This is a schematic flowchart of a specific embodiment of the method for preparing a perovskite solar cell module according to the present invention.

[0019] Figure 2 This is a schematic diagram of a specific embodiment of the perovskite solar cell module of the present invention. Detailed Implementation

[0020] The present application will now be described in further detail with reference to the accompanying drawings and embodiments. Through these descriptions, the features and advantages of the present application will become clearer and more apparent.

[0021] The term “exemplary” as used herein means “serving as an example, embodiment, or illustration.” Any embodiment illustrated herein as “exemplary” is not necessarily to be construed as superior to or better than other embodiments. Although various aspects of embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless specifically indicated otherwise.

[0022] Furthermore, the technical features involved in the different embodiments of this application described below can be combined with each other as long as they do not conflict with each other.

[0023] In a first aspect, the present invention relates to a method for preparing a perovskite solar cell module, the method comprising the following steps: a perovskite semi-dry film preparation step: forming a perovskite wet film on a first charge transport layer by perovskite ink, and then subjecting the perovskite wet film to low-temperature pre-crystallization to obtain a perovskite semi-dry film; wherein the low-temperature pre-crystallization temperature is 30-55°C and the time is 1-10 min; a laser scribing step: performing laser scribing on the perovskite semi-dry film to obtain a perovskite film with laser scribing grooves.

[0024] It should be noted that the low-temperature pre-crystallization temperature can be 30-35℃, 35-40℃, 40-50℃, 50-53℃, etc., preferably around 50℃, and the preferred time is 1-5 minutes; or the temperature can be around 50-58℃, or around 62-70℃. The perovskite solar cell module preparation method of this invention is applicable to the preparation of large-area perovskite solar cell modules. The low-temperature pre-crystallization process forms a gel-like semi-dry film with a small amount of solvent, which can effectively suppress the generation of edge burrs, burn marks, and dust during laser etching or scribing, effectively reducing or minimizing laser scribing damage. It causes less damage to the film, with no burrs or burn marks, while minimizing dust formation. More importantly, the well-defined edges of the perovskite film facilitate the dense deposition of charge extraction layers and buffer layers, which is beneficial for improving battery efficiency and long-term stability.

[0025] It should be noted that low-temperature pre-crystallization of the perovskite wet film forms a semi-dry film with a certain mechanical strength. This semi-dry film's state is between that of a dry film and a wet film. While it contains some organic solvents and is not as dry as a dry film, it possesses structural strength and does not exhibit the strong fluidity and diffusion of a wet film. Because the semi-dry film contains a suitable amount of organic solvents, P2 laser scribing causes less damage, resulting in no burrs or craters, and minimizes dust formation. The regular laser-cut surface formed during P2 laser scribing is also more conducive to the uniform coverage of the charge extraction layer and buffer layer.

[0026] According to a specific embodiment of the preparation method described in the first aspect of the present invention, the preparation method further includes a high-temperature annealing step after the laser scribing step: subjecting the perovskite film with laser scribing grooves to high-temperature annealing to obtain a high-temperature annealed perovskite film.

[0027] It should be noted that high-temperature annealing and crystallization can remove the remaining organic solvent in the film, resulting in a perovskite dry film with P2 scribing grooves. Simultaneously, some of the damage caused to the perovskite semi-dry film during the P2 laser scribing process is repaired during high-temperature annealing and crystallization, which is beneficial for improving battery efficiency and long-term stability.

[0028] According to a specific embodiment of the preparation method described in the first aspect of the present invention, the high-temperature annealing temperature is 100-150°C and the time is 1-30 min.

[0029] According to another specific embodiment of the preparation method described in the first aspect of the present invention, the chemical formula of the perovskite material in the perovskite film after high-temperature annealing is ABX3, wherein A is selected from FA. + MA + and Cs + One or more combinations of B, where B is Pb 2+ and / or Sn 2+ X is selected from CI - ,Br - and I - One or more combinations thereof.

[0030] It should be noted that the chemical formula of the perovskite material ABX3 can be represented as FA. 1-x-y MA x Cs y Pb 1-m Sn m (I 1-p-q Br p Cl q )3, where x, y, m, p and q are each independently selected from values ​​greater than or equal to 0 and less than or equal to 1.

[0031] According to a specific embodiment of the preparation method described in the first aspect of the present invention, the perovskite ink is prepared by mixing raw materials containing AX, BX2 and a solvent, wherein the minimum concentration of A, B and 1 / 3 of X in the perovskite ink is 0.7-2 mol / L.

[0032] It should be noted that the concentrations of A, B, and 1 / 3 of X can all be 0.7-2 mol / L, or the lowest concentration among the three can be 0.7-2 mol / L, while the concentrations of the other one or two can be greater than 2 mol / L.

[0033] It should be noted that after mixing the raw materials containing AX, BX2, and solvent, it is assumed that all A, B, and X in the mixture are converted into ABX3, and the molar concentration of ABX3 is 0.7-2 mol / L. For example, if the molar concentrations of A and B in the mixture are 1 mol / L and the molar concentration of X is 3 mol / L, then the molar concentration of ABX3 is 1 mol / L; if the molar concentrations of A and B in the mixture are 2 mol / L and the molar concentration of X is 3 mol / L, then the molar concentration of ABX3 is 1 mol / L; if the molar concentrations of A and B are 3 mol / L and the concentration of 1 / 3 of X is 1 mol / L, then the molar concentration of ABX3 is 1 mol / L. Therefore, within the above numerical range, the concentration of ABX3 is the minimum of the molar concentrations of A, B, and 1 / 3 of X. In summary, by controlling the minimum concentration of A, B, and 1 / 3 of X to be 0.7-2 mol / L, the molar concentration of ABX3 in the mixture is 0.7-2 mol / L.

[0034] According to another specific embodiment of the preparation method described in the first aspect of the present invention, the thickness of the perovskite film after high-temperature annealing is 1-5000 nm and the band gap is 1.2-2.3 eV.

[0035] It should be noted that the band gap is a concept directly related to the conversion efficiency of photovoltaic materials. It refers to the energy required to release electrons from the material and make them charge carriers (i.e., freely moving charged particles that transport current through movement) to flow in a circuit. When preparing perovskite inks or perovskite precursor solutions, the band gap of the perovskite material in the final thin film can be controlled within a certain range by controlling the proportions of different materials in the raw materials.

[0036] According to a specific embodiment of the preparation method of the first aspect of the present invention, the preparation method further includes the following steps after the high-temperature annealing step: sequentially preparing a second charge transport layer, a buffer layer, and a second electrode on the perovskite film after the high-temperature annealing; and / or, the preparation method further includes the following steps before the perovskite semi-dry film preparation step: preparing the first charge transport layer on the first electrode, and then performing laser scribing on the first charge transport layer; or, performing laser scribing on the first electrode, and then depositing the first charge transport layer.

[0037] It should be noted that after P1 scribing of the first electrode, such as an FTO transparent conductive glass substrate, the substrate can be cleaned with water or ethanol. After the second charge transport layer, buffer layer, and second electrode are sequentially prepared on the perovskite film after high-temperature annealing, P3 scribing can be performed to obtain the component.

[0038] It should be noted that the first electrode and the second electrode are each independently selected from transparent glass electrodes and metal electrodes. The first electrode and the second electrode can both be transparent glass electrodes, or both can be metal electrodes, or one can be a transparent glass electrode and the other a metal electrode. The thickness of the first electrode and the second electrode is independently 1-1000 μm. The buffer layer can be one or more layered combinations of metal oxides, organic ammonium salts, long-chain alkylamines, and aliphatic amines; the metal oxide can be SnO2, etc.; the preparation methods of the buffer layer include, but are not limited to, thermal evaporation, coating, sputtering, and spraying.

[0039] As a variation of the implementation, when the first electrode is transparent conductive glass, a transparent conductive oxide layer can also be provided, such as SnO2, etc. By providing this transparent conductive oxide layer, better charge transport performance can be achieved.

[0040] According to another specific embodiment of the preparation method described in the first aspect of the present invention, the first charge transport layer and the second charge transport layer are respectively selected from different types of electron transport layers and hole transport layers. The first charge transport layer and the second charge transport layer are each independently prepared by solution method, thermal evaporation method, sputtering method, or atomic layer deposition method. And / or, the hole transport layer comprises NiO. x The electron transport layer is selected from one or more combinations of CuFeO2, CuAlO2, CuSCN, Cu2O, WO3, CuI2, MoS2, FeS2, P3HT, Spiro-meoTAD, Spiro-TTB, Poly-TPD, PFN, PEDOT, PSS, and PTAA, where 0.1 ≤ x ≤ 10. And / or, the electron transport layer is selected from TiO2, SnO2, ZnO, ZrO2, In2O3, CdS, CdSe, BaSnO3, Nb2O5, C 60 A combination of one or more of PCBMs.

[0041] It should be noted that the first charge transport layer can be an electron transport layer, and correspondingly, the second charge transport layer is a hole transport layer; or, the first charge transport layer can be a hole transport layer, and correspondingly, the second charge transport layer is an electron transport layer.

[0042] It should be noted that the thicknesses of the first charge transport layer and the second charge transport layer are each independently 0.1-1000 nm.

[0043] In another specific embodiment of the preparation method according to the first aspect of the present invention, the first electrode and the second electrode are each independently selected from one or more combinations of Cu, Al, Ag, Au, ITO, IZO, FTO and IWO.

[0044] It should be noted that the first electrode and the second electrode can be transparent electrodes, i.e., conductive glass electrodes and metal electrodes, respectively; as a specific embodiment, the first electrode and the second electrode can both be transparent electrodes, or both can both be metal electrodes; as a specific embodiment, when one of the electrodes is a transparent electrode, a metal electrode can be disposed on it, or when one of the electrodes is a metal electrode, a transparent electrode can be disposed on it.

[0045] It should be noted that the preparation method described in the first aspect of the present invention can be described in the following order:

[0046] (1) P1 scribing is performed on FTO or ITO transparent conductive glass substrate using a laser, with a line width of 40-100um, and the substrate is cleaned.

[0047] (2) A charge extraction layer is prepared on the substrate surface in step (1). In this invention, the charge extraction layer is preferably one of a hole transport layer or an electron transport layer.

[0048] (3) Prepare a perovskite wet film based on the charge extraction layer in step (2). The deposition methods of the perovskite wet film include, but are not limited to, blade coating, spraying, slot coating, inkjet printing, etc.

[0049] (4) The perovskite wet film obtained in step (3) is subjected to low-temperature annealing and pre-crystallization to form a semi-dry film; the annealing temperature can be 30-70℃, 50-70℃, or 30-55℃, or 40℃, 41.5℃, 42℃, 43.5℃, 45℃, 48.5℃, 51℃, 53℃, 56℃ and 58℃, etc., and the annealing time is preferably 1-5min;

[0050] (5) Perform P2 laser scribing on the perovskite semi-dry film prepared in step (4) to form regular grooves with a certain structural strength, and then perform annealing to form a perovskite dry film.

[0051] (6) A charge transport layer 2, a buffer layer, and an electrode layer are prepared on the dry film obtained in step (5) to form a complete perovskite solar cell. P3 lines can also be scribed on the perovskite solar cell to obtain a module.

[0052] The preferred deposition methods for the charge transport layer, buffer layer, and electrode material involved in this invention are one or a combination of magnetron sputtering, ALD, and thermal evaporation.

[0053] In a second aspect, the present invention relates to a perovskite solar cell module, which is obtained by the preparation method described in the first aspect of the present invention.

[0054] The present invention will be further described in detail below through examples, but these examples are not intended to limit the invention. Unless otherwise specified, all reagents and apparatus used in the following examples are commercially available finished products.

[0055] Example 1

[0056] (1) P1 scribing was performed on the FTO transparent conductive glass substrate using a laser with a line width of 50um, and the substrate was cleaned with water, isopropanol and ethanol.

[0057] (2) A 25 nm nickel oxide hole transport layer is deposited on the substrate surface in step (1) by magnetron sputtering;

[0058] (3) Using a mixed solvent of N,N-dimethylformamide DMF and dimethyl sulfoxide DMSO with a volume ratio of 7:3 as the solvent, based on PbI2, PbBr2, FAI and MABr, a perovskite precursor ink FAPbI3 (concentration ratio 0.95) and MAPbBr3 (concentration ratio 0.05) with a total concentration of 1.5 mol / L were prepared. The perovskite was then deposited on the charge extraction layer (hole transport layer) in step (2) by coating.

[0059] (4) The perovskite wet film obtained in step (3) is subjected to low-temperature annealing and pre-crystallization to form a semi-dry film; the annealing temperature can be 50°C and the annealing time is preferably 1 min.

[0060] (5) P2 laser scribing is performed on the perovskite semi-dry film prepared in step (4) to form regular grooves with a certain structural strength, and then annealing is performed at 120℃ for 20 min to form a perovskite dry film; the thickness of the perovskite dry film is 600 nm and the band gap is 1.53 eV.

[0061] (6) Prepare a charge transport layer C on the dry film obtained in step (5). 60 (evaporation method), buffer layer SnO2 (atomic deposition method) and electrode layer Ag (evaporation method) form a complete perovskite cell.

[0062] (7) Draw a P3 line on the perovskite cell obtained in step (6) to obtain the module.

[0063] Comparative Example 1

[0064] (1) P1 scribing was performed on the FTO transparent conductive glass substrate using a laser with a line width of 50um, and the substrate was cleaned with water, isopropanol and ethanol.

[0065] (2) A 25 nm nickel oxide hole transport layer is deposited on the substrate surface in step (1) by magnetron sputtering;

[0066] (3) Using a mixed solvent of DMF and DMSO with a volume ratio of 7:3 as the solvent, based on PbI2, PbBr2, FAI and MABr, a perovskite precursor ink FAPbI3 (concentration ratio of 0.95) and MAPbBr3 (concentration ratio of 0.05) with a total concentration of 1.5 mol / L were prepared. The perovskite was then deposited on the charge extraction layer (hole transport layer) in step (2) by coating.

[0067] (4) The perovskite wet film obtained in step (3) is subjected to high-temperature annealing crystallization. The annealing temperature can be 150℃ and the annealing time is preferably 10min. After annealing, a perovskite dry film is formed. The thickness of the perovskite dry film is 600nm and the band gap is 1.53eV.

[0068] (5) Perform P2 laser scribing on the perovskite dry film prepared in step (4) to form regular grooves with a certain structural strength;

[0069] (6) Prepare a charge transport layer C on the dry film obtained in step (5). 60 The perovskite solar cell is formed by vapor deposition, with a buffer layer of SnO2 (atomic deposition) and an electrode layer of Ag (vapor deposition).

[0070] (7) Draw a P3 line on the perovskite cell obtained in step (6) to obtain the module.

[0071] Comparative Example 2

[0072] (1) P1 scribing was performed on the FTO transparent conductive glass substrate using a laser with a line width of 50um, and the substrate was cleaned with water, isopropanol and ethanol.

[0073] (2) A 25 nm nickel oxide hole transport layer is deposited on the substrate surface in step (1) by magnetron sputtering;

[0074] (3) Using a mixed solvent of DMF and DMSO with a volume ratio of 7:3 as the solvent, based on PbI2, PbBr2, FAI and MABr, a perovskite precursor ink FAPbI3 (concentration ratio of 0.95) and MAPbBr3 (concentration ratio of 0.05) with a total concentration of 1.5 mol / L were prepared. The perovskite was then deposited on the charge extraction layer (hole transport layer) in step (2) by coating.

[0075] (4) P2 laser scribing is performed on the perovskite wet film prepared in step (3) to form regular grooves with a certain structural strength, and then annealing is performed at 120℃ for 20 min to form a perovskite dry film; the thickness of the perovskite dry film is 600 nm and the band gap is 1.53 eV.

[0076] (5) Prepare a charge transport layer C on the dry film obtained in step (4). 60 The perovskite solar cell is formed by vapor deposition, with a buffer layer of SnO2 (atomic deposition) and an electrode layer of Ag (vapor deposition).

[0077] (6) Draw a P3 line on the perovskite cell obtained in step (5) to obtain the module.

[0078] Test Implementation Examples

[0079] The short-circuit current density Jsc, voltage Voltage, fill factor FF, and photoelectric conversion efficiency of the components prepared in the above embodiments and comparative examples were tested using the IV curve test method. The results are shown in Table 1 below.

[0080] Table 1

[0081] <![CDATA[Jsc(mA / cm 2 )]]> Voltage (V) FF Efficiency Example 1 2.78 9.21 0.78 19.97096 Comparative Example 1 2.76 9.1 0.74 18.58584 Comparative Example 2 2.74 8.76 0.73 17.52175

[0082] Compared to laser etching of the perovskite dry film in Comparative Example 1 and laser scribing of the perovskite wet film in Comparative Example 2, laser scribing of the semi-dry perovskite film in Example 1 of this application effectively suppresses the generation of edge burrs, burn marks, and dust during the laser scribing process, effectively reducing laser scribing damage. The film suffers less damage, with no burrs or burn marks, achieving better results in repairing laser scribing damage. Simultaneously, dust formation is minimized during the process, and the well-defined edges of the perovskite film facilitate the dense deposition of charge extraction and buffer layers. Furthermore, as shown in Table 1 above, compared to P2 laser scribing based on the perovskite dry film or the perovskite wet film in the comparative examples, laser scribing based on the semi-dry film in this application improves the photoelectric conversion efficiency and other performance characteristics of the resulting battery module.

[0083] In the description of this application, it should be noted that the terms "upper", "lower", "inner", "outer", "front", "rear", "left", "right", etc., indicate the orientation or positional relationship based on the orientation or positional relationship in the working state of this application. They are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.

[0084] In the description of this application, it should be noted that, unless otherwise expressly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. Those skilled in the art can understand the specific meaning of these terms in this application based on the specific circumstances.

[0085] The present application has been described above with reference to preferred embodiments; however, these embodiments are merely exemplary and illustrative. Various substitutions and modifications can be made to the present application based on these embodiments, all of which fall within the protection scope of the present application.

Claims

1. A method for preparing a perovskite solar cell module, characterized in that, The preparation method includes the following steps: Perovskite semi-dry film preparation steps: A perovskite wet film is formed on the first charge transport layer by perovskite ink, and then the perovskite wet film is subjected to low-temperature pre-crystallization to obtain a perovskite semi-dry film; wherein the low-temperature pre-crystallization temperature is 30~55℃ and the time is 1-10min; Laser scribing steps: Laser scribing is performed on the perovskite semi-dry film to obtain a perovskite film with laser scribing grooves.

2. The preparation method according to claim 1, characterized in that, The preparation method further includes a high-temperature annealing step following the laser scribing step: The perovskite film with laser-etched grooves is subjected to high-temperature annealing to obtain a high-temperature annealed perovskite film.

3. The preparation method according to claim 2, characterized in that, The high-temperature annealing temperature is 100-150℃, and the time is 1-30 minutes.

4. The preparation method according to claim 2 or 3, characterized in that, The chemical formula of the perovskite material in the perovskite film after high-temperature annealing is ABX3, where A is selected from FA. + MA + and Cs + One or more combinations of B, where B is Pb 2+ and / or Sn 2 + X is selected from CI - ,Br - and I - One or more combinations thereof.

5. The preparation method according to claim 4, characterized in that, The perovskite ink is prepared by mixing raw materials containing AX, BX2 and a solvent. In the perovskite ink, the minimum concentration of A, B and 1 / 3 of X is 0.7-2 mol / L.

6. The preparation method according to claim 2, characterized in that, The thickness of the perovskite film after high-temperature annealing is 1~600nm and the band gap is 1.2~2.3eV.

7. The preparation method according to claim 2, characterized in that, The preparation method further includes the following steps after the high-temperature annealing step: A second charge transport layer, a buffer layer, and a second electrode are sequentially prepared on the perovskite film after high-temperature annealing; and / or, The preparation method also includes the following steps prior to the perovskite semi-dry film preparation step: The first charge transport layer is fabricated on the first electrode, and then laser scribing of the first charge transport layer is performed; or, Laser scribing is performed on the first electrode, and then the first charge transport layer is deposited.

8. The preparation method according to claim 7, characterized in that, The first charge transport layer and the second charge transport layer are each selected from different types of electron transport layers and hole transport layers; the first charge transport layer and the second charge transport layer are each independently prepared by solution method, thermal evaporation method, sputtering method or atomic layer deposition method; and / or, The hole transport layer contains NiO. x One or more combinations of CuFeO2, CuAlO2, CuSCN, Cu2O, WO3, CuI2, MoS2, FeS2, P3HT, Spiro-meoTAD, Spiro-TTB, Poly-TPD, PFN, PEDOT, PSS, and PTAA, wherein 0.1 ≤ x ≤ 10; and / or, The electron transport layer is selected from TiO2, SnO2, ZnO, ZrO2, In2O3, CdS, CdSe, BaSnO3, Nb2O5, C 60 A combination of one or more of PCBMs.

9. The preparation method according to claim 7, characterized in that, The first electrode and the second electrode are each independently selected from one or more combinations of Cu, Al, Ag, Au, ITO, IZO, FTO and IWO.

10. A perovskite solar cell module, characterized in that, The perovskite solar cell module is obtained by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Perovskite thin film and preparation method thereof

    CN107331778A

  • Perovskite solar cell and preparing method of the same

    KR102260293B1